HUBUNGAN PENGGUNAAN TIKTOK SEBAGAI MEDIA REFERENSI KONTEN TERHADAP KREATIVITAS MAHASISWA KOMUNIKASI DIGITAL DAN MEDIA SEKOLAH VOKASI IPB - Manoppo, Nathaniela Anya Jeconia; Wahyu Budi Priatna; Rici Tri Harpin Pranata; Sutisna Riyanto (Jurnal Netnografi Komunikasi, 2025)
The rapid dominance of TikTok among Generation Z students has shifted consumption patterns, positioning it as a primary source of creative reference. This phenomenon poses a dilemma between mere imitation and genuine originality in the academic creative process. This study aims to analyze the correlation between using TikTok as a content reference medium and the creativity of Digital Communication and Media students at IPB Vocational School. A quantitative correlational survey approach was employed with a sample of 77 active students determined by random sampling. Data analysis utilized the Spearman correlation technique due to non-normal distribution, revealing a significant and moderately strong positive correlation between the two variables (r = 0.562, p = 0.001). This positive correlation is primarily driven by the students' high Creative Self-Efficacy (CSE) and the effective use of TikTok to boost Fluency and Flexibility dimensions. Creativity is actualized when students engage in Redefinition by recontextualizing viral trends, confirming that the platform acts as a constructive creative tool when supported by a strong internal drive.